Clinical and Instrumental Evaluation of the Effectiveness of Surgical Treatment of Chronic Generalized Periodontitis Using RANK-RANKL-OPG Biomarkers - Elbek A. Gaybullaev1, Jasur A. Rizaev1, Bekhzod Sh. Abdullaev1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The problem of clinical and instrumental evaluation of the surgical treatment effectiveness of chronicgeneralized periodontitis using RANK-RANKL-OPG biomarkers is discussed in the article. Currently,the important role of Pro - and anti-inflammatory cytokines in the regulation of the immune-inflammatoryresponse has been established 2. Progressive destruction of bone tissue in patients with periodontal diseases isassociated with a combination of cytokines IL-1?, IL-6, TNF and prostaglandins E2. The use of Alhadaya incomplex therapy with surgical treatment will allow to control the level of biomarkers of bone inflammation,which will allow to use this method for the diagnosis of periodontal diseases and as the outcome of treatment,in addition to traditional research method (clinical, functional, x-ray, densitometric).